2012
DOI: 10.1038/srep00557
|View full text |Cite
|
Sign up to set email alerts
|

SNP in starch biosynthesis genes associated with nutritional and functional properties of rice

Abstract: Starch is a major component of human diets. The relative contribution of variation in the genes of starch biosynthesis to the nutritional and functional properties of the rice was evaluated in a rice breeding population. Sequencing 18 genes involved in starch synthesis in a population of 233 rice breeding lines discovered 66 functional SNPs in exonic regions. Five genes, AGPS2b, Isoamylase1, SPHOL, SSIIb and SSIVb showed no polymorphism. Association analysis found 31 of the SNP were associated with differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
85
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 99 publications
(90 citation statements)
references
References 38 publications
4
85
0
1
Order By: Relevance
“…Climate change adds to the difficulty of achieving the necessary rates of genetic gain (Abberton et al ., 2016). The wild relatives of rice provide a gene pool that allows for the expansion of diversity (Krishnan et al ., 2014) in domesticated rice for the creation of new high yielding genotypes, with new nutritional and functional traits (Kharabian‐Masouleh et al ., 2012) and adaptation to new environments (Brozynska et al ., 2016). The A genome species of Oryza , which include the species that are readily interfertile with rice, represent the effective primary gene pool for rice.…”
Section: Introductionmentioning
confidence: 99%
“…Climate change adds to the difficulty of achieving the necessary rates of genetic gain (Abberton et al ., 2016). The wild relatives of rice provide a gene pool that allows for the expansion of diversity (Krishnan et al ., 2014) in domesticated rice for the creation of new high yielding genotypes, with new nutritional and functional traits (Kharabian‐Masouleh et al ., 2012) and adaptation to new environments (Brozynska et al ., 2016). The A genome species of Oryza , which include the species that are readily interfertile with rice, represent the effective primary gene pool for rice.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of starch biosynthetic enzymes on starch properties have been studied, and various relationships between starch biosynthesis and properties have been proposed [93,102]; however, these relationships are indirect, as environmental factors including water, temperature, and light are also involved in starch biosynthesis. Understanding the fine structures of starch has the potential to give in-depth information on starch biosynthesis [31,202,204].…”
Section: Introductionmentioning
confidence: 99%
“…Rice grain shape has been described to be simultaneously controlled by triploid endosperm genes, cytoplasmic genes, embryo and maternal plant genes (Shi and Zhu, 1996;Shi et al, 2000). Studies by Kharabian-Masouleh et al, 2012 andTan et al, 1999 reported that rice starch is controlled in the waxy gene region. Tian et al, 2005 reported that cooked rice elongation is also likely controlled in the waxy gene region.…”
Section: Introductionmentioning
confidence: 99%